Letter - Moor Row Strike Committee, 7 May 1926 (page 1) (Moor Row)
1926-05-07 "Letter - Moor Row Strike Committee, 7 May 1926 (page 1)" [g0081001.jpg], 7 May 1926, Moor Row Strike Committee Local Organisation